Halal procurement strategy in the food industry in Indonesia - Indriansyah, Albertty; Irfany, Mohammad Iqbal; Tieman, Marco (Halal Studies and Society, 2024)
Indonesia is a Muslim-majority country with significant potential to develop a solid halal industry. A critical area for growth in this sector is halal procurement, which has been observed to remain under-researched, particularly in the Indonesian context. Therefore, this study aims to address the gap by identifying challenges and proposing strategic solutions for halal procurement in the food industry of the nation. To achieve the stated objective, data was collected through expert interviews, Analytical Network Process (ANP) was adopted as the decision-making methodology, and Strength, Weakness, Opportunity, and Threat (SWOT) analysis was carried out. The results showed that strength factor was the first priority in advancing halal procurement in food sector in Indonesia. Specifically, the most influential factors identified include the availability of raw materials, the lack of value-added commodities, the guarantee of continuous raw material supply, and the presence of numerous global competitors, all of which served as the strength, Weakness, Opportunity, and Threat to the halal food industry.